The Invisible Hand of Rent Seeking: Capitalism, Democracy, and the Budget Deficits - Hayakawa, Hiroaki; P. Venieris, Yannis (Journal of Reviews on Global Economics, 2017)
Historically, social and economic grievances resulted in sociopolitical instability, which served as a medium of institutional changes in the evolution of Western Europe toward a more inclusive regime. In today’s democratic capitalism, however, a great many interest groups have burgeoned and acquired political power to seek their own interest at the expense of the welfare of the general public. Interest groups thrive on a tacit agreement with those members of the political body whose primary interest lies in their own aggrandizement. Such agreement inevitably leads to excessive claims on public resources, interferes with the market system by perpetuating rent in many sectors of the economy, erodes the moral values of trust and respect, and causes moral hazard among the legislators by undermining budgetary discipline. Moreover, the inevitable friction among the legislators often results in gridlock in public decision making. The democratic capitalism thus is losing on both ends: the market efficiency and political efficacy, with reduced prospect of economic growth. This paper attempts to explain these phenomena as a strategic equilibrium of the major players in the politico-economic arena.